Creepy White Gaze: Rethinking the Diorama as a Pedagogical Activity - Sterzuk, Andrea; Mulholland, Valerie (Alberta Journal of Educational Research, 2011)
Drawing on gaze and postcolonial theory, this article provides a theoretical discussion of a problematic photograph published in a provincial teachers’ newsletter. The photo consists of a White settler child and two White settler educators gathered around his heritage fair entry diorama entitled “Great Plains Indians.” This article analyzes this image to gain a better understanding of how curriculum and pedagogical activities work discursively to produce dominant and dominated racial positions in Saskatchewan. Reposant sur un regard et sur une théorie postcoloniale, cet article offre une discussion théorique d'une photographie inquiétante publiée dans un bulletin provincial pour enseignants. La photo représente un enfant et deux enseignants, tous des pionniers blancs, entourant le diorama que l'élève a préparé pour une célébration du patrimoine et qui s'intitule « Great Plains Indian ». Nous analysons cette image afin de mieux comprendre l'effet discursif des activités pédagogiques sur la production de positions raciales dominante/dominée en Saskatchewan.